(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The growing use of artificial intelligence (AI) in education has redefined approaches to foreign language learning and teaching. In English language education, AI technologies are being integrated to support communicative competence through adaptive learning environments, intelligent feedback, and interactive practice. This paper explores methodological principles guiding the integration of AI in English teaching and analyzes its pedagogical impact on developing learners’ communicative abilities. The study highlights the significance of personalization, collaboration, and reflection as essential methodological foundations that ensure technology supports rather than replaces human instruction. The findings suggest that when properly designed, AI-assisted learning environments can enhance linguistic performance, pragmatic awareness, and learner autonomy—key dimensions of communicative competence.